Management accounting practice at Beximco Pharmaceuticals Ltd.: a review of costing function - Sarwar, Syeda Afrina (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2011.